Finding the fish : using hydroacoustics to track forage fish off the coast of Central California - Thayne, Michael W., 1983- (2016)
Verkefnið er unnið við Háskólasetur Vestfjarða Verkefnið er lokað til 30.9.2017. Forage fish are a crucial link between primary producers and the success of many top marine predators in pelagic ecosystems around the world. In upwelling systems such as the California Current Ecosystem (CCE), forage fish availability can be the central determining factor in the survival of upper trophic level species, and their young. Northern anchovy (Engraulis mordax) and juvenile rockfish serve as a critical conduit for the transfer of energy to top marine predators in the CCE. This study used acoustic descriptors of anchovy schools and juvenile rockfish (Sebastes spp.) to identify them in hydroacoustic data collected from 2004 to 2015 in the Greater Farallones and Cordell Bank National Marine Sanctuaries in the CCE. Anchovy-like schools were detected using a mean volume backscattering strength of -44.8 dB (SE ± 0.69). Juvenile rockfish-like single targets were detected using a target strength (TS) range between -52.8 to -50.9 dB. The TS range was calculated using estimated and measured lengths of juvenile rockfish consumed by three piscivorous seabirds. The lengths of the fish were put through a length dependent TS model to derive the TS for juvenile rockfish. The results of the acoustic analysis were used to derive acoustic abundance indices of both forage fish species. To verify the acoustic methods, the acoustic indices were compared to trawling data collected by the National Oceanic Atmospheric Administration and the diets collected from the common murre, rhinoceros auklet, and Brandt‘s cormorant. The results suggest that the acoustic methodologies used can accurately track the presence of both forage fish species. Point Blue Conservation Science